Design of a DVI video receiver chip - Gu Hong; Fang Zhen (Dianzi Jishu Yingyong, 2022)
In this paper, a DVI(Digital Visual Interface) receiver chip is designed and an all-digital-based T.M.D.S signal reception recovery scheme is proposed. This scheme can greatly reduce the design difficulty of PLL and the hardware overhead of the chip.This paper firstly introduces the whole frame of this chipand functionof each module, and then emphasizes the principle and realization of data recovery circuit based on this scheme, and finally conducts relative discussion on simulation and test results. The test results indicates that, this chip which meets the requirements of DVI 1.0 specification, can be compatible with other DVI products and communicate with them.